Citrulline in health and disease. Review on human studies. Issue 6 (December 2018) - Papadia, Cinzia; Osowska, Sylwia; Cynober, Luc; Forbes, Alastair
Summary: The amino acidL -citrulline (CIT) is safely used from the neonatal period onwards in those with urea cycle defects and carbamyl phosphate synthetase or ornithine transcarbamylase deficiencies, but several lines of enquiry indicate that it might have a much wider therapeutic role. When protein intake is low and there is a catabolic state, endogenous arginine (ARG) synthesis cannot fully be met and its supplementation can prove challenging, particularly in patients with critical and multisystem illness. Supplementary CIT could constitute a safer but still focused means of delivering ARG to endothelial and immune cells as CIT is efficiently recycled into these cells and as kidneys can convert CIT into ARG. Unlike ARG, CIT is efficiently transported into enterocytes and bypasses liver uptake. It also appears to prevent excessive and uncontrolled nitric oxide (NO) production. Animal studies and early human data indicate positive effects of CIT on protein synthesis, in which its contribution is thought mediated through the mTOR pathway. It appears that CIT is an anabolic pharmaconutrient that can be safely administered even in critically ill patients. Promising results in cardiovascular diseases and in disease-related malnutrition can now be considered sufficient to justify formal clinical exploration in these areas and in sarcopenia in general.